TEKNOLOGI PROSES PEMBUATAN MESIN PENCETAK ADONAN KUE KACANG INTIP DENGAN SISTEM ROLL CUTTING KAPASITAS 10 KG/JAM - Ritonga, Abdul Rahman; Mahyunis, Mahyunis; Mahadi, Batu; supryadi, supryadi (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
From the results of the design of the peanut cake molding machine with a roll cutting system capacity of 10 kg / hour, obtained several main components namely 2 pieces of pressing roll, 1 set of cutting blades 1 set of conveyor belts, 2 roll conveyors and other supporting components such as gears, bearings , chain, reducer, frame and drive motor, the next step is to determine the work steps of making components and determining the tooling equipment used, among others, making the frame using steel ruler, sawing machine, welding machine and hand grinding. Manufacture of drive shaft using a sawing machine, and lathe, press roll making, using cutting saws and welding machines, manufacturing of blades, cutting grinding machines, welding machines, and hand grinding, the manufacture of inlets using hand grinding machines and welding machines, manufacture of outlet using hand grinding machines and welding machines. From the results of calculating the component manufacturing and assembly processes, the frame is 5.49 (hours), drive shaft 200.08 (minutes), press roll 2.42 (hours), roll conveyor 2.42 (hours), blade 20, 65 (hours) inlet 1.68 (hours), outlet 1.39 (hours) and assembly 5.88 (hours). Based on the analysis of the results of the actual manufacturing time for 43.67 (hours) the actual time for the process of making the printing machine for peanut cake dough for 43.67 (hours). If the engine work efficiency is estimated to be 80% or (0.80), the machining time becomes 43.67: 0.80 = 54.58 (hours).